Supramolecular Coordination Polymers by Self-assembling of Bis-monodentate Ligands with HgI(2) - Li, Xiaokang (Molecular Diversity Preservation International (MDPI), 2007)
Two supramolecular coordination polymers, [HgI(2)(L(1))·0.5H(2)O](∞) (1) and [HgI(2)(L(2))·0.4CH(3)OH](∞) (2), have been prepared by ligands L(1) (L(1) = bis[4-(4- pyridylmethyleneamino)phenyl] ether) and L(2) (L(2) = N,N′-bis(3-pyridylmethyl)-diphthalic diimide) with HgI(2), respectively. 1 formed an interestingly infinite cross-linked double helical structure, whereas 2 formed the one-dimensional zigzag chains, which are parallel with each other.